Projeto AJA-Expansão e os desafios para o enfrentamento do analfabetismo entre jovens adultos e idosos em Goiânia - Ferro, Maria Margarida de Santana Ferreira (2019)
This dissertation, which is linked to the Research Line Work, Education and Social Movements, of the Graduate Program in Education of the Faculty of Education of the Federal University of Goiás, aimed to investigate the AJA-Expansion project as a proposal for young people, adults and the elderly, from the Goiânia Municipal Secretariat of Education (MSE / Goiania), implemented from 2001 to 2008. The research aimed to understand the historicity of AJA and the role it played in expanding or not the right of access to education for young people and adults (EYA). We opted for a qualitative approach of bibliographic and documentary character. The investigation included analysis of official documents and research related to the theme, as well as interviews with educators and project managers, along with SME / Goiânia, and professors from partner universities, who collaborated in the process of creation and initial training of popular educators and coordinators. This literacy experience sought to reprint those from 1993 to 1996, as an attempt to insert the principles of popular education into school spaces. These principles were experienced by Paulo Freire through the Culture Circles in the 1960s, and were taken up in many experiences in the context of EYA in Brazil after the end of the Military Regime. The research on the AJAExpansion Project of MSE / Goiânia is inserted in the context of attempts to intervene in educational policies and reflections on how these policies have been constituted throughout history, understanding that everyone has the right to quality education, without exception as provided for in the Federal Constitution of 1988. To follow the path of this investigation we used works by: Avelar (2017), Brandão (1984, 2008), Freire (1987), Leite (2015), Machado (1997), (2009), Nunes (2016), Rodrigues (2000, 2008), Rummert and Ventura (2007), Weffort (1967), among others. The documentary sources were obtained from the Municipal Education Secretariat of Goiânia (MSE) and from the Centro Memória Viva: Documentation and Reference in Youth and Adult Education (EYA), Popular Education and Social Movements in the Midwest Region (CMV). The results show that, despite the recognition of the AJA-Expansion Project as a strategy to confront illiteracy in Goiânia, among the young, adult and elderly population, there wasn’t a consolidation of the Project as a State policy, which was revealed in the difficulties of articulation between the federal and municipal spheres, when the Municipality of Goiânia joined the Brazil Literate Program (BLP); the lack of commitment of municipal managers to continue the project, which aimed to consolidate popular education as part of the education system; and the continuous non-expansion of enrollment in the initial series of EYA in MSE / Goiânia, main objective propagated by the AJA-Expansion Project.